Komunikasi Organisasi dalam Pengkaderan pada Anggota Dewan Perwakilan Mahasiswa Universitas Muhammadiyah Palangkaraya - Sirajul Rahman; Aldi Firdaus (PT. PENERBIT TIGA MUTIARA, 2023)
Communication is a fundamental aspect of human life that enables individuals to connect and interact with one another. In the context of an organization, communication plays a crucial role in building effective relationships among its members. Harold Lasswell described communication as a process that can be explained through the following questions: “who says what in which channel to whom with what effect?” This question highlights the complexity of communication within an organization, which is also relevant for study in organizations such as the Student Representative Council of Muhammadiyah University of Palangkaraya, especially in the context of significant changes that are taking place. This study aims to understand the dynamics of communication in the cadre training process between the management and members of the organization. The primary focus of the research is to explore how communication occurs between the management and members during cadre training activities. This research uses a qualitative approach with a descriptive type, along with data collection techniques involving interviews and documentation. To ensure data validity, the researcher employs triangulation of sources, techniques, and time. The findings of the study show that communication in the cadre training process is divided into two categories: internal and external communication. Internal communication involves interactions between the management and members within the organization, with freedom in conveying information between leaders, managers, and members. Meanwhile, external communication focuses on the relationship between the organization and other institutions, to convey aspirations in accordance with its tasks and authority. Additionally, the cadre system in this organization combines both formal and informal training, although there are differences in how each faculty representative conducts cadre training. Overall, this organization is able to implement a more optimal cadre system, especially in preparing the core management.